Representasi Gegar Budaya dalam Novel Edensor - Dewi Insyiroh; Dea Gitta Darda; Majidatun Nur Aini; Mohamad Afrizal (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This article analyzes the representation of culture shock in Andrea Hirata's novel Edensor, focusing on the experiences of the main characters, Ikal and Arai, as they interact with European culture. Using Kalvero Oberg's culture shock theory, which includes the stages of honeymoon, crisis, recovery, and adjustment, this study explores how both characters undergo shifts in mindset and attitudes when confronted with foreign cultural values. The paper also discusses the impact of culture shock on their character development and its relevance in today's global socio-cultural context, including migration and international education. Through this analysis, it is understood that culture shock is not merely a clash of cultures, but also a crucial process for learning and personal growth. The findings of this study are expected to contribute to interdisciplinary literary studies, particularly in understanding the relationship between literature and social-cultural phenomena.